Exploring the Influence of Self-Competence and Islamic Boarding School Regulations on Student Character: The Mediating Role of Islamic Boarding School Culture - Setyani, Mamik; Asyrofi Yahya, Fata; Wit Daryono, Rihab; Thoriquttyas, Titis (Cendekia: Kependidikan dan Kemasyarakatan, 2024)
This research explores the influence of self-competence and boarding school regulations on character development through Islamic boarding school culture. The probability sampling method was used to collect data from 42 PPTQ Al-Muqorrobin students. The data was collected using questionnaires that employ a Likert scale with 4 answer choices. After that, a PLS-SEM analysis was conducted to test the model concepts. The analysis found that manners and ethics were the main indicators of student character success, contributing to 98.70%. The results also showed that Islamic boarding school regulations and culture positively influence students' character formation. Self-competences, both academic and social, also have a significant influence. This finding means that increased self-efficacy makes students more independent and confident in facing challenges. Progress increases academic motivation and self-confidence, while social skills strengthen positive interactions and create empathy and tolerance attitudes. It shows that increasing student self-efficacy has individual benefits and contributes to students’ character development.